Evasão escolar no ensino técnico subsequente: percepção dos professores do Instituto Federal do Acre - Campus Rio Branco - Silva, Milton Euclides da (2020)
The general objective of this researching is analyze, from the docent’ perception, the motivation that explain or justify the evasion in the subsequent technical courses of administration and human resources offered in the Federal Institute of Acre, campus Rio Branco, in order to propose for reducing of school truancy, the development of a process of monitoring students during academic journey, as well as the organization offer of training courses of professor, to conduct of research, three docents were interviwed and their speechs were organized from the categories of individual perception (the professor) and those related to institional perception (the school) using Prose Analysis as formulated by Andre as a method (1983). The analyzes on reasons for school truancy has a theoretical support the studies of Dore and Luscher (2011). Dore Araújo and Mendes (2014), Rumberger (2011), Rumberger and Lim (2008), Addis (2017), in addiction to official documents issued by the researched institution. The results pointed to the predominance of a perception about school truancy that considers them such as: docent training to work in professional education; Identification with the course; need to work docents perspective; teaching practice; dificulties faced by students in the course and processes of pedagogy practices